Abortion and infanticide: why the parent-child relationship symmetry breaker fails - Holt, Joshua William (Journal of medical ethics, 2025)
Some pro-life philosophers have argued that if one accepts abortion, one should accept infanticide. Prabhpal Singh has proposed a symmetry breaker. He argues that the parent-child relationship can only be obtained between born humans and such a relationship entails that infanticide is wrong. I consider this account and argue that not only is its central claim, that only born humans can stand in a parent-child relationship, unmotivated, but even if accepted, it would still not explain why infanticide is wrong.